The media swirl politics, audiovisuality, and aesthetics - Vernallis, Carol (Duke University Press, 2023)
From fan-generated content on TikTok to music videos, the contemporary media landscape is becoming ever more vast, spectacular, and intense. In The Media Swirl Carol Vernallis examines short-form audiovisual media-Beyoncé's Lemonade, brief sequences from Baz Luhrmann's Great Gatsby, TikTok challenges, YouTube mashups, commercials, and many other examples-to offer ways of understanding digital media. She analyzes music videos by Beyoncé, Lady Gaga, Janelle Monáe, Kendrick Lamar, Anderson .Paak, and others to outline how sound and image enhance each other and shape a viewer's mood. Responding to today's political-media landscape through discussions of Fox News and Presidential inaugurations, Vernallis shows how a media literacy that exceeds newscasts and campaign advertising is central to engaging with the democratic commons. Forays into industry studies, neuroscience, and ethics also inform her readings. By creating our own media and knowing what corporations, the wealthy, and the government do through media, Vernallis contends that we can create a more just world
Keywords: SOCIAL SCIENCE / Media Studies; Digital media -- Social aspects; Mass media and culture; Mass media -- Political aspects; Mass media -- Social aspects; Music videos -- Social aspects; Social media and society; Spectacular, The, in motion pictures